NADI: the pulse that start the art / Muhamad Hafiz Hassan ... [et al.] - Hassan, Muhamad Hafiz; Mohd Razali, Noraziah; Pindah, Chrisna; Hishamuddin, Nurul Amy Azura; Michael, Valerie; Mohd Rathi, Mohd Razif; Abu Bakar, Muhammad Fauzan (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
At the very core of academics is the creative energy that motivates, directs, and unites us all. As lecturers, we are guardians of inspiration, encouraging the heartbeat of creativity in our students, as art and design instructors, rather than just imparters of information. I am delighted to present this group effort, which is the result of seven illustrious coworkers' knowledge and dedication, to you. NADI: The Pulse That Start The ART is a very important and deep notion in the fields of graphic design and fine arts, and their combined efforts have resulted in an extraordinary collection devoted to this topic. Readers will find a tour of the basic concepts that form the basis of the art and design disciplines on these collaborations. Every chapter showcases the many viewpoints and life experiences of our respected authors, weaving together a wealth of knowledge that guides both students and lecturers. 'NADI' goes beyond technique and explores the core of creativity via the rhythmic cadence of line and shape and the dynamic interaction of colour and composition. This book is like a map; it shows the way through the maze of creative expression with purpose and clarity via careful analysis, introspective contemplation, and practical advice. It is our deepest conviction as educators that we are entrusted with the mission of nurturing not just our pupils' intellectual capacities, but also their enthusiasm, creativity, and individuality. 'NADI' exemplifies this philosophy by giving students the tools they need to tap into their own creativity and transform their dreams into real, meaningful art. I really hope that this book will spark conversations, investigations, and new ideas at the art and design schools where the youth of today will grow up. The book should be alive with imagination, encouraging everyone who sees them to believe in the life-altering potential of art and design. I urge you to join me on this adventure of discovery, where the rhythm of creation reverberates in each stroke of the brush, each pixel, and each flash of inspiration, with my sincerest appreciation for the priceless contributions of my fellow educators.